CONSUMPTION AND INDUSTRIAL DEMAND FOR FRUIT JUICES AND CONCENTRATES - Štrbac, Maja; Savić, Mirjana (Economics of Agriculture, 2010)
The market of food products in the EU there is great competition. Consumers significantly "dictated" by changes in products and innovative solutions. The trend of healthy lifestyles, increasing consumer interest in exotic flavors and an attractive organic food, are the main reasons for the observed increase in fruit juice market. Manufacturing companies in the EU also have a demand for fruit juices and concentrates, the more you require a guaranteed product quality continuously/safe products and safe delivery of fresh products. Producers in developing countries have great opportunities for marketing their products in the markets of developed countries, if they meet certification requirements, which is often complicated, and for many producers/exporters is very expensive. Certified producers and exporters will have access to much of the market. Producers in developing countries should explore possibilities for placement of products in each EU country, as some member countries/trading partners can be attractive for certain products.